Nickel export ban policy in Indonesia - a path to sustainable economic development? - Setiani, Hastin; Valennia, Risca; Rusni, Nur Khafifah (EcoProfit: Sustainable and Environment Business, 2024)
Electric-based vehicles (EV) come as an option for the solution over the GHG emissions problem resulting from energy production and transportation. Background. The demand for nickel, as a vital component of the lithium-ion batteries used in EV increases significantly and Indonesia plays a critical role as the owner of the world's largest nickel reserve. While exporting raw materials can increase national income, Indonesia misses out on the opportunity to capture higher value-added benefits from downstream processing and manufacturing. The nickel export ban policy is proposed by the Indonesian government as an effort to encourage the growth of the domestic nickel processing industry and capture higher value from the country’s nickel resources. From the creation of domestic value addition, industrial development, and sustainable resource management, it is hoped that Indonesia will move toward sustainable economic development. Methods. This paper reviewed component required to assess the nickel export strategy for long-term economic growth. We used a straightforward approach, outlining each sustainability principle's underlying objectives and providing justifications for why it should be considered in the nickel sector. By citing justifications for their advantages and justifications for their risks, we analyzed the existing policy. Results and discussions. Indonesia's nickel sector does not comply with sustainability principles and is used as a raw material for electric vehicle batteries, but it may only benefit a few people rather than the general welfare of the community. Conclusion. Therefore, the government's decision to impose a ban on nickel exports is correct, but it must be accompanied by efforts to improve both in terms of technology and policies regarding natural resource management. To control the power inclination to ensure sustainability and equality that sustainable natural resource management promotes, further study of the political component is required.